“NO VIRAL NO JUSTICE”: KETIDAKSESUAIAN FAKTA HUKUM DENGAN FAKTA MEDIA SOSIAL DALAM PERSPEKTIF SOSIOLOGI HUKUM - Nataningrum, Nanindya; Subarsyah, Teddy (Gapenas Publisher, 2025)
Law enforcement often only occurs after an event goes viral on social media, indicating that the legal system reacts responsively to public pressure, rather than based on objective normative mechanisms. Law enforcement should be carried out based on the principles of legality, justice, and independence of legal institutions, without relying on media exposure or mass opinion. The purpose of this study is to analyze in depth how the influence of virality on social media can affect the independence and objectivity of law enforcement in Indonesia, as well as to examine the impact of the discrepancy between legal facts and social media facts on the legal decision-making process from a legal sociology perspective. This research method uses a qualitative method with a juridical-sociological approach, namely examining law as part of a social phenomenon influenced by the development of society, especially social media. Data were collected through library studies and documentation of scientific literature, laws and regulations, online news, and social media content related to viral cases that reflect the imbalance between legal facts and social facts. The results of this study indicate that the Influence of Virality on social media on the Independence and Objectivity of Law Enforcement in Indonesia can threaten the independence and objectivity of law enforcement in Indonesia because it creates strong public pressure on law enforcement officers. In a viral situation, law enforcers tend to be motivated to respond quickly to public opinion, which has the potential to ignore the principles of evidence and legal procedures that should be carried out neutrally and professionally. The Inconsistency Between Legal Facts and Social Media Facts in the Perspective of Legal Sociology shows the complexity of the relationship between law, society, and information technology. The influence of social media on legal decision-making requires the adaptation of the legal system so that it can continue to uphold justice objectively and socially accepted. This requires a deep understanding of social and legal interactions and the application of appropriate technology to maintain a balance between legal facts and social facts in the digital era.